SYNTHESIS, PHYSICAL PROPERTIES AND TOXICITY STUDIES OF IONIC LIQUIDS TO PREDICT THE HAZARD POTENTIAL ON HUMAN AND THE ENVIRONMENT - HOSSAIN, MOHAMMAD ISMAIL (2012)
The toxicities of the synthesised ILs were measured using three different species which were: fish, bacteria and human cells. Fish are the important consumers in the aquatic food chain, and they play a vital role in keeping the aquatic ecosystem balanced. Therefore, it is necessary to determine the toxicity of the ILs on fish when the impact of the ILs on the aquatic environment is evaluated. The acute toxicity of imidazolium and ammonium ILs was evaluated against a freshwater organism: Guppy fish, Poecilia reticulata. The LC5os were determined according to the Organisation for Economic Co-operation and Development (OECD) guideline 203 (fish acute toxicity test) and found to be in the range of 36.30 to 177.83 mgL- 1 , which lay on a slightly toxic to practically non-toxic basis on the acute toxicity rating scale by the Fish and Wildlife Service (FWS).